American anthropology in Micronesia : an assessment - Kiste, Robert C., 1936-; Marshall, Mac (University of Hawaiì Press, 1999)
"American Anthropology in Micronesia: An Assessment evaluates how anthropological research in the Trust Territory has affected the Micronesian people, the U.S. colonial administration, and the discipline of anthropology itself. Contributors analyze the interplay between anthropology and history, in particular how American colonialism affected anthropologists' use of history, and examine the research that has been conducted by American anthropologists in specific topical areas of socio-cultural anthropology. Although concentrating largely on disciplinary concerns, the authors consider the connections between work done in the era of applied anthropology and that completed later when anthropology was pursued mainly for its own sake. The focus then returns to applied concerns in more recent years and issues pertaining to the relevance of anthropology for the world of practical affairs. It will be of essential interest to students and scholars of Pacific Islands studies and the history of anthropology."--Jacket